Strategi Meningkatkan Motivasi Belajar Siswa Sekolah Dasar Melalui Media Pembelejaran Berbasis Teknologi: Literatur Review - Hendri; Hubbi Saufan Hilmi (LPPM Institut Pendidikan Nusantara Global, 2026)
Learning motivation is a decisive factor in successful learning, especially for elementary students who easily disengage from monotonous conventional methods. Technological advances allow teachers to present more engaging, interactive learning media. This study systematically examines strategies for enhancing elementary students' learning motivation through technology-based media, using a literature review of national scientific articles published 2014–2025. Findings show that interactive multimedia, instructional videos, animated media, e-learning, and gamification consistently contribute positively to students' motivation, both intrinsic and extrinsic, with effectiveness depending on media suitability, teachers' digital competence, and supporting infrastructure. This review also identifies implementation challenges such as infrastructure gaps, limited teacher digital literacy, and regional access disparities. The study concludes that technology integration must be designed with attention to motivational principles such as the ARCS Model and Self-Determination Theory to achieve optimal impact.